The Effect Of Perforation On The Dynamics Of A Flexible Panel - Putra, Azma; Cheah, Yee Mun; Muhammad, Noryani; Ahmad Rivai; Wai, Chee Mun (Hindawi, 2014)
Introduction of holes into plate-like structures is commonly found as one of the practical noise control measures to reduce sound radiation. However, perforation also reduces the panel stiffness and hence increases its vibration. The discussion on this effect is lacking and hence this paper discusses the dynamics of a perforated panel from the results obtained from Finite Element (FE) model. Different hole geometries and arrangement are simulated to investigate their effect on the plate mobility. In general, it is found that increasing the perforation ratio increases the plate mobility. For a fixed perforation ratio, the mobility increases at high frequency (above 1kHz) for a smaller hole density in the plate. The plate with holes concentrated at the middle shows the largest increase of vibration around the plate centre compared to those uniformly distributed or away from the middle and concentrated at the plate edges. This is because as the hole separation becomes smaller, the reduction of the global stiffness around the mid area of the plate becomes greater. This also corresponds to the finding here that the mobility is greater at the vicinity of the hole. Different conditions of the plate edges are found to give consistent trend of the effect of perforation.